The Relationship among the Inspiratory Muscle Strength, the Perception of Dyspnea and Inhaled Beta2-Agonists in Patients with Asthma - Paltiel Weiner; Rasmi Magadle; Marinella Beckerman; Noa Berar-Yanay (Canadian Respiratory Journal)
BACKGROUND: It is well documented that the perception of dyspnea (POD), subjectively reported by patients, is related to the activity and strength of the inspiratory muscles, and influences the use of 'as needed' beta2-agonists.